2019
DOI: 10.1080/13467581.2019.1696205
|View full text |Cite
|
Sign up to set email alerts
|

Energy uncertainty of manual solar shades for different window-to-wall ratios

Abstract: Manual solar shades rely on occupants' control and thus its energy performance is highly related to occupants' behavior. This paper conducted a co-simulation study on the impact of shade behavior on building energy performance and its uncertainty at different window-to-war ratios (WWRs). A previously developed stochastic behavior model for manual solar shades is used in this paper. Results show that energy uncertainty increases from 1.8% to 3.5% as WWR increases from 25% to 90% and a linear regression was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Equation () is a formula for calculating the deflection value, 41 where P is the load value corresponding to the classification, a is the shear span length of 1080 mm, l is the span of 3250 mm, and α is the ratio of the shear span to the span, a / l = 0.3323.…”
Section: Materials and Test Methodsmentioning
confidence: 99%
“…Equation () is a formula for calculating the deflection value, 41 where P is the load value corresponding to the classification, a is the shear span length of 1080 mm, l is the span of 3250 mm, and α is the ratio of the shear span to the span, a / l = 0.3323.…”
Section: Materials and Test Methodsmentioning
confidence: 99%
“…The minimum number of repeated simulations required is defined by the point at which the line (the cumulative mean of the simulated annual energy demand) becomes flat. In this paper, 100 simulation runs were conducted and the mean value of the fitted distribution was considered as the true mean energy demand since previous research has confirmed that this number was enough for determining the distribution of energy data (Gilani, O'Brien, and Gunay 2018;Yao 2019;Macdonald 2009).…”
Section: Distribution Of Energy Performancementioning
confidence: 99%
“…This model has the benefits of considering partial shading states and was validated with realistic shade behavior patterns in that building. Energy, thermal, visual and life cycle economic performance of manual shades have been studied (Yao 2014;Yao 2018a;Yao, Chow, and Chi 2016;Yao 2019;Yao and Zheng 2019). This paper is a continuation of previous research and the focus of the current research is: (1) to compare shading performance difference between east, south and west facades; (2) to compare the difference in energy performance and uncertainty levels among the three facades; and (3) to determine the minimum number of simulation runs to obtain reliable annual energy and peak heating/cooling loads at different building scales.…”
Section: Introductionmentioning
confidence: 99%